Pengaruh Kondisi Keuangan Perusahaan, Sosialisasi Perpajakan, dan Sanksi Perpajakan pada Kepatuhan Wajib Pajak Hotel - Deinara, Nyoman Nadia Naissa; Jati, I Ketut (E-Jurnal Akuntansi; Vol 27 No 2 (2019)DO - 10.24843/EJA.2019.v27.i02.p21, 2019)
Compliance with taxpayers is the most important aspect in the taxation system in Indonesia which adheres to a self-assessment system that provides trust in calculating, paying, and reporting on the amount of tax payable. This study aims to empirically examine the effect of corporate financial conditions, tax socialization, and tax sanctions on hotel taxpayer compliance. This research uses primary data by distributing questionnaires. The population is all active hotel taxpayers registered with the Regional Revenue Agency of Badung Regency, which is 2,456 hotels. The method of determining the sample used is the accidental sampling method using the Slovin formula, so that a sample of 96 hotels was obtained with a 5 year observation year. The analysis technique uses multiple linear regression analysis. Based on the results of the analysis, it was found that the company's financial condition, tax socialization, and tax sanctions had a positive effect on hotel taxpayer compliance. Keywords: Financial conditions, tax socialization, tax sanctions, tax compliance